A (Mo2 / 3Y1 / 3)2AlB2 i-MAB material and its self-propagating synthesis and stepwise purification method

CN123026445APending Publication Date: 2026-11-03SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611270272.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies are difficult to effectively prepare (Mo2/3Y1/3)2AlB2 i-MAB materials, especially since impurity phases are prone to appear during the self-propagating high-temperature synthesis process and are difficult to remove, resulting in insufficient formation of the target phase or difficulty in purification.

Method used

A self-propagating high-temperature synthesis was carried out using a Ti-C-assisted exothermic system and a method of physical isolation between the raw materials and the Mo-Y-Al-B reaction. Subsequently, the impurity phase content was reduced by stepwise purification through HCl acid washing and NaOH/H2O2 alkaline oxidation to obtain high-purity (Mo2/3Y1/3)2AlB2 i-MAB material.

Benefits of technology

We achieved rapid preparation of high-purity (Mo2/3Y1/3)2AlB2 i-MAB material, reducing dependence on external heating, improving the generation efficiency of the target phase, and significantly reducing the content of impurity phases through stepwise purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026445A_ABST
    Figure CN123026445A_ABST
Patent Text Reader

Abstract

The application discloses a (Mo2 / 3Y1 / 3)2AlB2 i-MAB material and a self-propagating synthesis and step-by-step purification method thereof, and belongs to the technical field of layered boride ceramic material preparation. The application prepares raw materials according to Mo:Y:Al:B=4:2:3(1+x):6, and is loaded in isolation from a Ti-C auxiliary exothermic system. The Ti-C system is ignited in an argon atmosphere, and the self-propagating reaction of the Mo-Y-Al-B raw materials is induced by using the heat release, so that a crude product containing an i-MAB main phase is obtained. The crude product is sequentially subjected to HCl acid washing and NaOH / H2O2 alkaline oxidation treatment, so as to reduce the contents of Y2O3, MoAlB and MoB impurity phases. After purification, the content of the target phase is about 92.02%, and no Y2O3 and MoAlB independent diffraction peaks are detected. The method can quickly synthesize the target i-MAB main phase and obtain a powder material with a high target phase content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of preparation technology of layered boride ceramic materials, specifically relating to a (Mo2 / 3Y1 / 3)2AlB2i-MAB material and its self-propagating synthesis and stepwise purification method. Background Technology

[0002] MAB phase materials are a class of layered borides composed of transition metal elements (M), A-site elements, and B elements. Their crystal structure typically consists of alternating layers of transition metal boride structural units and A-elements. The i-MAB phase is a quaternary layered boride with in-plane chemical order at the M-site; (Mo2 / 3Y1 / 3)2AlB2 belongs to this class. These materials possess both some metallic and ceramic properties and can serve as precursors for the preparation of two-dimensional transition metal borides, making them valuable for research in functional ceramics and electrochemical energy storage.

[0003] Currently, (Mo2 / 3Y1 / 3)2AlB2 is mainly prepared using high-temperature solid-state reaction or spark plasma sintering. High-temperature solid-state reaction typically requires high reaction temperatures and long holding times; spark plasma sintering relies on dedicated heating and pressurizing equipment. Both methods require continuous external energy input, placing certain demands on reaction equipment and process control. For other MAB phases, studies have employed rapid reaction methods such as thermal explosion and self-propagating high-temperature synthesis. However, the reaction heat effects, liquid phase formation rules, element volatilization behaviors, and competing phase formation mechanisms differ significantly among different material systems, meaning that process parameters for other MAB phases cannot be directly applied to the Mo-Y-Al-B quaternary i-MAB system.

[0004] Self-propagating high-temperature synthesis primarily utilizes the heat released by the reaction system to sustain reaction propagation, characterized by faster reaction times and reduced reliance on prolonged external furnace heating. However, this process is influenced by factors such as the system's exothermic capacity, heat loss, powder contact state, and reaction kinetics. For systems with insufficient exothermic capacity or complex reaction pathways, direct ignition may only induce localized reactions, leading to insufficient reaction propagation or limited formation of the target phase. To improve effective heat input, preheating or the installation of auxiliary exothermic systems can be employed. However, if the auxiliary exothermic substance is directly mixed with the target raw material, its reactants or products may enter the target product, increasing the difficulty of subsequent separation and purification. Summary of the Invention

[0005] Given the lack of a self-propagating high-temperature synthesis method for (Mo2 / 3Y1 / 3)2AlB2i-MAB materials in existing technologies and the potential for multiple and numerous impurities in the synthesized products, this invention provides a (Mo2 / 3Y1 / 3)2AlB2i-MAB material and its self-propagating synthesis and stepwise purification method. This invention establishes a self-propagating synthesis route suitable for the Mo-Y-Al-B quaternary system, and reduces the content of the main impurity phases through post-treatment adapted to the phase composition of the self-propagating crude product, thereby obtaining i-MAB powder materials with a high content of the target phase.

[0006] This invention uses Mo, Y, Al, and B powders as reactants and employs a Ti-C-assisted exothermic system, physically isolated from the target raw materials, to provide heat and induce a self-propagating high-temperature synthesis reaction in the Mo-Y-Al-B system, obtaining a crude product containing the target i-MAB main phase. Subsequently, based on the phase composition of different impurity phases in the crude product and their different responses to chemical media, HCl acid washing and NaOH / H2O2 alkaline oxidation treatment are performed sequentially to reduce the content of impurity phases such as Y2O3, MoAlB, and MoB, thereby obtaining an i-MAB powder material with a high content of the target phase.

[0007] The overall technical route of this invention is divided into two main modules: self-propagating high-temperature synthesis and stepwise directional purification. First, the (Mo2 / 3Y1 / 3)2AlB2 i-MAB main phase is rapidly generated through a self-propagating reaction. Then, impurities are removed stepwise targeting the unique impurity combination of the crude product, increasing the relative content of the target phase while retaining its main characteristic diffraction peaks. The specific implementation steps are as follows:

[0008] Technical solution: This invention provides a self-propagating synthesis and stepwise purification method for (Mo2 / 3Y1 / 3)2AlB2 i-MAB material, comprising the following steps:

[0009] S1. Weigh Mo powder, Y powder, Al powder and B powder according to the composition relationship of (Mo2 / 3Y1 / 3)2AlB2 to prepare the Mo-Y-Al-B reaction raw material system; then ball mill the mixture.

[0010] Mo, Y, Al, and B are weighed according to a molar ratio. Based on the chemical composition of (Mo2 / 3Y1 / 3)2AlB2, the theoretical molar ratio of Mo, Y, Al, and B can be expressed as 4:2:3:6. When Al is in excess, the molar ratio of Mo, Y, Al, and B can be expressed as 4:2:3(1+x):6, where x is the excess ratio of Al and x is greater than 0.

[0011] Preparation of S2 and Ti-C assisted exothermic system;

[0012] S3. Loading: Lay boron nitride-coated carbon cloth on the inner wall of the crucible, fill the area around the crucible with the Ti-C auxiliary exothermic system, and fill the center area of ​​the crucible with the Mo-Y-Al-B reaction raw material system. Press lightly to keep the powder in stable contact, so that the Mo-Y-Al-B reaction raw material system and the Ti-C auxiliary exothermic system are physically isolated and thermally coupled. Embed a spiral tungsten wire laterally in the Ti-C auxiliary exothermic system as an ignition element.

[0013] S4. Self-propagating synthesis and collection of crude product: Under an argon atmosphere, the Ti-C assisted exothermic system is ignited by an external electric ignition to induce an exothermic reaction. The heat released by the Ti-C assisted exothermic system is used to induce a self-propagating high-temperature synthesis reaction in the Mo-Y-Al-B reaction raw material system to obtain a crude product containing the (Mo2 / 3Y1 / 3)2AlB2 i-MAB main phase.

[0014] S5. The crude synthetic product is pulverized, and the pulverized product is placed in HCl solution for acid washing to remove or reduce the content of Y2O3 and MoAlB impurity phases. After solid-liquid separation, the acid-washed solid product is obtained.

[0015] S6. The acid-washed solid product is placed in a NaOH / H2O2 mixed solution for alkaline oxidation treatment to further reduce the residual MoB content.

[0016] S7. The solid product after alkaline oxidation treatment is washed, separated into solid and liquid and dried to obtain (Mo2 / 3Y1 / 3)2AlB2 i-MAB material (layered boride material).

[0017] S1-S4 are the self-propagating high-temperature synthesis stages, and S5-S7 are the stepwise purification stages.

[0018] Furthermore, in S1, the purity of the Mo powder, Y powder, Al powder, and B powder is not less than 99.9%, and the particle size is 300 mesh or equivalent.

[0019] Furthermore, in S1, the excess Al ratio x is 4% to 30%, preferably 20%.

[0020] Further, in step S1, the weighed Mo powder, Y powder, Al powder, and B powder are placed in a planetary ball mill for mixing. The ball milling speed is 240 r / min, the ball milling time is 6 h, the ball-to-powder ratio is 3:1, and argon gas is introduced into the ball mill jar for 20 min before ball milling to reduce the risk of powder oxidation during the ball milling process. After ball milling, the mixed powder is taken out and passed through a 200-mesh sieve for later use.

[0021] Furthermore, in S2, a Ti-C auxiliary exothermic system is set as the ignition heat source, consisting of Ti powder and C powder, with a molar ratio of Ti to C of 1:1. The purity of both Ti powder and C powder is 99.9%, and the particle size is 300 mesh or equivalent. The Ti-C auxiliary exothermic system is ball-milled and sieved according to the method in S1.

[0022] Furthermore, in S4, the argon atmosphere treatment method is as follows: the crucible containing the Ti-C auxiliary exothermic system and the Mo-Y-Al-B reaction raw material system is placed in a vertical self-propagating reactor, and three vacuum-purging-argon-filling cycles are performed. Each time, the vacuum is purged to approximately −0.1 MPa; the first two cycles are filled with argon gas with a purity of not less than 99.999% to 0.1 MPa, and the last cycle is filled with argon gas to 0.35 MPa. All pressures mentioned are gauge pressures.

[0023] Furthermore, in S4, the ignition voltage of the electric ignition method is 5-40V, the ignition time is 1min, and the ignition voltage is preferably 10V.

[0024] Furthermore, in S4, after the Ti-C system is exothermic, a self-propagating high-temperature synthesis reaction of the Mo-Y-Al-B raw material in the central region is induced by heat transfer. After the reaction ends and the mixture is naturally cooled to room temperature, the crucible is removed, and the Ti-C reaction residue and carbon cloth on the periphery are removed. Only the crude product from the central region of the crucible is collected. XRD characterization shows that the crude product is mainly composed of (Mo2 / 3Y1 / 3)2AlB2 i-MAB, and also contains impurity phases such as MoB, Y2O3, and MoAlB, and may contain a small amount of YMoB4 candidate residual phase.

[0025] Furthermore, in S5, the collected crude synthetic product is crushed, ground, and passed through a 200-mesh sieve, and the powder passing through the sieve is collected.

[0026] Furthermore, in step S5, the preferred acid washing conditions are: 10 mL of 2 mol / L HCl solution is added for every 1 g of sieved powder, and the mixture is stirred at 400 r / min for 24 h at room temperature. This step is mainly used to remove or reduce the content of Y₂O₃ and MoAlB impurity phases; however, MoB impurity phases still remain in the solid product after treatment.

[0027] Furthermore, in S6, the preferred alkaline oxidation treatment conditions are as follows: for every 1g of acid-washed solid product, a mixture prepared from 67mL of deionized water, 0.43g of 97% pure NaOH, and 2.8mL of 30% H2O2 is used, and the mixture is stirred at 400r / min for 4h at room temperature. This step aims to reduce the residual MoB phase, not to completely remove MoB.

[0028] Furthermore, in step S7, the solid product after alkaline oxidation is washed with deionized water until the pH is close to 7; the solid-liquid separation is performed by centrifugation at a speed of 3000-8000 r / min and a single centrifugation time of 2-5 min, preferably at a speed of 6000 r / min and a single centrifugation time of 3 min; the vacuum drying temperature is 50-80℃, preferably 60℃, and the drying time is preferably 24 h.

[0029] The method of this invention prepares (Mo2 / 3Y1 / 3)2AlB2 i-MAB material. After Rietzveld X-ray diffraction refinement analysis, the content of (Mo2 / 3Y1 / 3)2AlB2 i-MAB phase is not less than 90% within the range of crystalline phases involved in the refinement, and no obvious independent diffraction peaks of Y2O3 and MoAlB are detected.

[0030] Beneficial effects:

[0031] 1) This invention establishes a preparation route for the formation of the (Mo2 / 3Y1 / 3)2AlB2 i-MAB main phase by self-propagating high-temperature synthesis using Mo, Y, Al and B powders as reactants, providing a new method for the rapid preparation of this type of quaternary in-plane ordered layered boride.

[0032] 2) This invention adopts a self-propagating high-temperature synthesis method. After the reaction is started, the heat released by the auxiliary exothermic system and the target reaction system is mainly used to drive the reaction. The target i-MAB main phase can be formed in a short reaction process, reducing the dependence on long-term continuous heating of the external furnace.

[0033] 3) This invention uses the Ti-C system as an auxiliary heat source physically isolated from the Mo-Y-Al-B raw materials to improve the effective heat input of the target reaction system. Univariate control results show that under the experimental conditions, setting up the Ti-C auxiliary exothermic system can promote the formation of the target i-MAB phase. The physical isolation arrangement can reduce the direct contact between the auxiliary exothermic system and the target reaction raw materials, facilitating the separation of peripheral reaction residues after the reaction.

[0034] 4) By comparing the effects of different Al excess ratios and ignition voltages on the phase composition of the product, this invention determines that under the given raw material, filling and reaction conditions, an Al excess of 20% and an ignition voltage of 10 V are the optimal process conditions, resulting in clearer target phase characteristic diffraction peaks and relatively fewer impurity phase-related diffraction peaks.

[0035] 5) This invention targets impurity phases such as MoB, Y2O3, and MoAlB in the crude SHS product, employing a stepwise treatment route of first acid washing with HCl, followed by alkaline oxidation with NaOH / H2O2. XRD comparison results show that after HCl acid washing, the related diffraction peaks of Y2O3 and MoAlB are significantly weakened or no obvious independent diffraction peaks are detected. After further treatment, the related diffraction peaks of MoB are weakened, while the main characteristic diffraction peaks of the target i-MAB phase are still retained.

[0036] 6) The final stepwise purified sample was refined by X-ray diffraction Rietveld analysis. Within the range of crystalline phases involved in the refinement, the content of the target phase was about 92.02%, the content of MoB was about 7.18%, and there may be about 0.80% of YMoB4 candidate residual phase. This indicates that the method can convert the crude SHS product into i-MAB powder material with a high content of the target phase. Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the process flow for preparing (Mo2 / 3Y1 / 3)2AlB2 i-MAB material by inducing self-propagating high-temperature synthesis using a Ti-C assisted exothermic system and stepwise purification by HCl acid washing and NaOH / H2O2 alkaline oxidation.

[0038] Figure 2 The XRD patterns are shown for comparison of the original SHS product in Comparative Example 2, the HCl-washed product in Comparative Example 3, and the HCl-washed-NaOH / H2O2 alkaline oxidation product (final stepwise purified product) in Example 1.

[0039] Figure 3 The image shows the XRD Rietveld refinement results of the final stepwise purified product in Example 1.

[0040] Figure 4 The images show the SEM morphology, EDS mapping, and normalized atomic percentage of representative particles of the final stepwise purified product in Example 1; where (a) is the SEM morphology; (b) is the EDS mapping of Mo; (c) is the EDS mapping of Y; (d) is the EDS mapping of Al; (e) is the EDS mapping of B; and (f) is the normalized atomic percentage.

[0041] Figure 5 The XRD patterns of the original SHS products under different Al excess ratios in Example 2 are shown.

[0042] Figure 6 The XRD patterns of the original SHS products under different ignition voltage conditions in Example 3 are shown.

[0043] Figure 7 The XRD patterns of the products obtained in Comparative Example 1 with and without the Ti-C assisted exothermic system are shown in the figure. Detailed Implementation

[0044] The technical solution of the present invention will be described in detail below through embodiments, but the scope of protection of the present invention is not limited to the embodiments described.

[0045] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that the following embodiments are only used to illustrate specific implementation methods of the present invention and do not constitute a limitation on the scope of protection of the present invention. Without departing from the technical concept and expected technical effects of the present invention, those skilled in the art can make reasonable adjustments, combinations or equivalent substitutions to the relevant process parameters, operating steps and their connection methods according to actual needs.

[0046] It should be noted that the steps listed in this invention are used to illustrate the implementation process of the technical solution, and their numbering is only for ease of description and does not constitute a strict limitation on the order of implementation. Without affecting the technical effect, conventional auxiliary operations in the art may be added before, after, or between the steps. Unless otherwise specified, the raw materials, reagents, and equipment used in the embodiments can all be obtained through conventional commercial channels, and the related operations and tests can be completed using conventional methods in the art.

[0047] Figure 1 This is a schematic diagram of the process flow for preparing (Mo2 / 3Y1 / 3)2AlB2 i-MAB material by inducing self-propagating high-temperature synthesis using a Ti-C assisted exothermic system and stepwise purification by HCl acid washing and NaOH / H2O2 alkaline oxidation.

[0048] Example 1

[0049] The (Mo2 / 3Y1 / 3)2AlB2 i-MAB material was synthesized and purified stepwise under self-propagating conditions with 20% Al excess and ignition at 10V. The steps are as follows:

[0050] (1) Raw material preparation: Mo powder, Y powder, Al powder and B powder were weighed to prepare the Mo–Y–Al–B reaction raw material system. All the above powders were purchased from Qinghe County Huiji Metal Materials Co., Ltd., with a purity of 99.9% and a particle size of 300 mesh. According to the target phase integer stoichiometric ratio Mo:Y:Al:B=4:2:3:6, based on the theoretical total mass of 20g, the theoretical amount of Al was increased by 20%. Specifically, 10.850g of Mo powder, 5.027g of Y powder, 2.746g of Al powder and 1.834g of B powder were weighed, and the actual total mass of the resulting mixed powder was approximately 20.457g.

[0051] (2) Ball milling and mixing: The above powder was loaded into a stainless steel ball mill jar with a ball-to-powder ratio of 3:1. Argon gas was introduced for 20 minutes before ball milling, followed by closed ball milling at a speed of 240 r / min for 6 hours. After ball milling, the powder was passed through a 200-mesh sieve to obtain the Mo–Y–Al–B reaction raw material system.

[0052] (3) Preparation of auxiliary exothermic system: Weigh 40g of Ti powder and 10g of C powder to prepare Ti-C auxiliary exothermic system. The purity of both Ti powder and C powder is 99.9% and the particle size is 300 mesh. Ball mill and mix according to the conditions described in step (2), and pass through a 200 mesh sieve to obtain Ti-C auxiliary exothermic mixed powder.

[0053] (4) Loading: Lay boron nitride-coated carbon cloth inside the alumina crucible, fill the outer perimeter of the crucible with the Ti-C auxiliary exothermic system, and fill the central area of ​​the crucible with 10g of Mo-Y-Al-B reactants. Then, gently press and level the material manually using clean tools. Subsequently, a spiral tungsten wire is horizontally embedded in the Ti-C auxiliary exothermic system as an ignition element. The Ti-C auxiliary exothermic system is isolated from the central reactants.

[0054] (5) Atmosphere treatment: Place the crucible containing the sample in a vertical self-propagating reactor and perform three vacuum-argon purging cycles. Each time, vacuum is applied to approximately -0.1 MPa; for the first two cycles, argon gas with a purity of not less than 99.999% is purged to 0.1 MPa, and for the last cycle, argon gas is purged to 0.35 MPa. All pressures mentioned are gauge pressures.

[0055] (6) Self-propagating synthesis: The Ti-C assisted exothermic system was ignited by electric ignition at a voltage of 10V for 1 min. The Ti-C assisted exothermic system underwent an exothermic reaction, and through heat transfer, induced a self-propagating high-temperature synthesis reaction in the Mo-Y-Al-B reaction raw material system in the central region of the crucible. After the reaction was completed, the mixture was allowed to cool to room temperature naturally. The peripheral Ti-C reaction products and carbon cloth were removed, and only the synthesis product in the central region, i.e., the original SHS product, was collected.

[0056] XRD analysis revealed that the synthesized product was mainly composed of (Mo2 / 3Y1 / 3)2AlB2 i-MAB, and contained impurity phases such as MoB, Y2O3 and MoAlB, and possibly a small amount of YMoB4 candidate residual phase.

[0057] (7) HCl washing: The synthesized product in the central region is crushed, ground and passed through a 200-mesh sieve. 1g of the sieved powder is weighed and 10mL of 2mol / L HCl solution is added. The mixture is stirred at 400r / min for 24h at room temperature. After the treatment, the solid product is collected by centrifugation to separate the solid and liquid components.

[0058] (8) Washing of the acid-washed product: The solid product obtained in step (7) was repeatedly washed with deionized water until the pH of the supernatant was close to 7. After each wash, the solid product was centrifuged at 6000 r / min for 3 min to separate the solid and liquid. After washing, the obtained solid product was vacuum dried at 60℃ for 24 h to obtain the HCl-washed product.

[0059] (9) Alkaline oxidation treatment: Weigh 1g of the dried product after HCl washing, add a mixed treatment solution prepared by 67mL of deionized water, 0.43g of NaOH with a purity of 97% and 2.8mL of H2O2 with a mass fraction of 30%, and stir at 400r / min for 4h at room temperature to further reduce the content of residual MoB impurity phase.

[0060] (10) Washing and drying: After alkaline oxidation treatment, the obtained solid product was repeatedly washed with deionized water until the pH of the supernatant was close to 7; after each wash, the solid was separated by centrifugation at 6000 r / min for 3 min. After washing, the obtained solid product was vacuum dried at 60℃ for 24 h to obtain the stepwise purified (Mo2 / 3Y1 / 3)2AlB2 i-MAB material.

[0061] (11) Phase and morphology characterization: X-ray diffraction was used to analyze the phase of the original SHS product, the HCl-washed product and the final stepwise purified product, and Rietveld refinement was performed on the final stepwise purified product; scanning electron microscopy and energy dispersive spectroscopy were used to analyze the morphology, elemental distribution and local elemental composition of representative particles.

[0062] The XRD comparison diagrams of the original SHS product, the HCl-washed product, and the product after HCl-washed-NaOH / H2O2 alkaline oxidation treatment (final stepwise purified product) obtained in Example 1 are shown below. Figure 2 .Depend on Figure 2 It can be seen that after HCl acid washing, the characteristic diffraction peaks of Y2O3 and MoAlB impurity phases were significantly weakened or no obvious independent diffraction peaks were detected; after further alkaline oxidation treatment with NaOH / H2O2, the relevant diffraction peaks of the MoB impurity phase were further weakened, while the main characteristic diffraction peaks of the (Mo2 / 3Y1 / 3)2AlB2 i-MAB phase were still retained, indicating that stepwise purification treatment can reduce the content of the main impurity phases in the synthesized product.

[0063] The Rietveld refinement results of the final stepwise purified product are shown in [the table below]. Figure 3The sample exhibited characteristic diffraction peaks at 11.66°, 23.44°, 32.74°, 40.66°, and 49.04°, corresponding to the simulated standard spectrum of (Mo2 / 3Y1 / 3)2AlB2, and no obvious independent diffraction peaks for Y2O3 and MoAlB were detected. Three crystalline phases, (Mo2 / 3Y1 / 3)2AlB2, MoB, and YMoB4, were introduced into the refined model, with refined relative contents of approximately 92.02%, 7.18%, and 0.80%, respectively. YMoB4 was only used as a candidate residual phase for auxiliary semi-quantitative estimation. These results indicate that the final stepwise purified product is dominated by (Mo2 / 3Y1 / 3)2AlB2 i-MAB as the main crystalline phase.

[0064] The SEM morphology and EDS mapping results of representative particles of the final stepwise purified product are shown in the figure. Figure 4 Mo, Y, Al, and B elements are mainly distributed in the measured particle region and have a relatively consistent spatial distribution. The atomic percentages of Mo, Y, Al, and B are 27.17%, 12.98%, 19.71%, and 40.14%, respectively, which are basically consistent with the theoretical atomic percentages of Mo4Y2Al3B6 (26.67%, 13.33%, 20.00%, and 40.00%), indicating that the elemental composition of the representative particles of the measured sample is consistent with the theoretical composition of the target phase.

[0065] Example 2

[0066] This embodiment is used to investigate the effect of Al excess ratio on the formation of the (Mo2 / 3Y1 / 3)2AlB2 target phase. The specific steps are as follows:

[0067] (1) The Mo–Y–Al–B reaction raw material system was prepared according to the method described in Example 1, and the excess ratio of Al powder relative to the theoretical stoichiometric amount was set to 0%, 4%, 10%, 20% and 30%, respectively. Except for the excess ratio of Al, the total mass of raw materials, ball milling conditions, amount of Ti-C auxiliary exothermic system, filling method, reaction atmosphere, ignition voltage and ignition time of each group of samples were kept consistent.

[0068] (2) Self-propagating high-temperature synthesis was carried out according to the charging and ignition method described in Example 1. After the reaction was completed and cooled to room temperature, the original SHS product in the center area of ​​the crucible was collected. The products of each group were not subjected to HCl acid washing and NaOH / H2O2 alkaline oxidation treatment, and were directly tested by XRD.

[0069] XRD patterns of the original SHS products obtained with different Al excess ratios are shown in [reference needed]. Figure 5The spectra of each group were compared using the same testing range and data processing methods. The results showed that when the Al excess ratio was 20%, the characteristic diffraction peaks of the target phase in the obtained product were clearer, while the related diffraction peaks of the impurity phase were relatively fewer. When Al was not excessive, or when the excess ratio was too low or too high, the number of impurity peaks in the product increased relatively. Therefore, it was determined that under the reaction conditions described in this embodiment, an Al excess of 20% was the optimal mixing ratio.

[0070] Example 3

[0071] This embodiment is used to investigate the effect of ignition voltage on the ignition of the Ti-C assisted exothermic system and the formation of the target phase (Mo2 / 3Y1 / 3)2AlB2. The specific steps are as follows:

[0072] (1) The Mo–Y–Al–B reaction raw material system and the Ti-C auxiliary exothermic system were prepared according to the method described in Example 1, and ball milling, sieving, and loading were completed. The ignition voltage was set to 5V, 10V, 20V, and 40V, respectively, and the ignition time was 1min for each group of samples. Except for the ignition voltage, the raw material ratio, powder mass, ball milling conditions, loading method, and reaction atmosphere of each group of samples were kept consistent.

[0073] (2) The Ti-C assisted exothermic system was ignited using the above ignition voltage. After the reaction was completed and cooled to room temperature, the original SHS product in the center region of the crucible was collected. The products of each group were not subjected to further purification and were directly tested by XRD.

[0074] XRD patterns of the original SHS products obtained at different ignition voltages are shown in [reference needed]. Figure 6 The results show that when the ignition voltage is 10V, the characteristic diffraction peaks of the target phase in the product are relatively clear, while the related diffraction peaks of the impurity phase are relatively few; when the ignition voltage is 5V, 20V, or 40V, the impurity peaks in the product spectrum increase relatively or the peak shapes become more complex. Therefore, it is determined that under the reaction conditions described in this embodiment, 10V is a better ignition voltage.

[0075] Comparative Example 1

[0076] This comparative example is used to investigate the effect of the heat input provided by the Ti-C-assisted exothermic system on the formation of the (Mo2 / 3Y1 / 3)2AlB2 target phase. The specific steps are as follows:

[0077] (1) The Mo–Y–Al–B reaction raw material system was prepared according to the molar ratio of Mo:Y:Al:B = 4:2:3×1.04:6. The purity, particle size and ball milling conditions of the raw materials were the same as those in Example 1, that is, the ball-to-material ratio was 3:1. Argon gas was introduced for 20 min before ball milling, and ball milling was carried out for 6 h at 240 r / min. After ball milling, the mixture was passed through a 200 mesh sieve.

[0078] (2) A boron nitride-coated carbon cloth was laid in an alumina crucible, and the Mo-Y-Al-B mixed powder was filled into the central area of ​​the crucible. The powder was then manually pressed and leveled using clean tools, without using a press to form a blank. In this comparative example, no Ti-C auxiliary exothermic system was set up, and a spiral tungsten wire was directly embedded in the Mo-Y-Al-B mixed powder as an ignition element.

[0079] (3) Place the crucible in a vertical self-propagating reactor and perform three vacuum-argon purging cycles according to the conditions described in Example 1. Finally, purge with high-purity argon to 0.35 MPa and ignite with 10V for 1 min. After the reaction is complete and the mixture is allowed to cool naturally to room temperature, collect the product in the crucible for morphological observation and XRD testing.

[0080] The product obtained in this comparative example was compared with a sample having the same Al excess ratio of 4%, ball milling conditions, crucible, atmosphere treatment conditions, ignition voltage, and ignition time, but with a Ti-C assisted exothermic system. The only variable in the two sets of experiments was whether or not a Ti-C assisted exothermic system was used. The XRD comparison results are shown in [Figure number missing]. Figure 7 The results show that without the Ti-C assisted exothermic system, the product after the reaction is mainly in a loose powder state, with only a few strong diffraction peaks in its XRD pattern, and the overall correspondence with the simulated standard pattern of (Mo2 / 3Y1 / 3)2AlB2 is low. With the Ti-C assisted exothermic system, more characteristic diffraction peaks corresponding to the target phase appear in the product. Combining the morphology of the product after the reaction and the XRD results, it can be concluded that under the experimental conditions, the Ti-C assisted exothermic system is beneficial for increasing the effective heat input of the reaction system and promoting the formation of the (Mo2 / 3Y1 / 3)2AlB2 target phase.

[0081] Comparative Example 2

[0082] This comparative example illustrates the effect of stepwise purification on the content of impurity phases in the synthesized product.

[0083] Following the method described in Example 1, a self-propagating high-temperature synthesis with Ti-C assisted heat input was performed to obtain the original SHS product containing the (Mo2 / 3Y1 / 3)2AlB2 main phase. After crushing, grinding, and passing through a 200-mesh sieve, the product was directly subjected to XRD analysis without HCl washing or NaOH / H2O2 alkaline oxidation treatment.

[0084] The XRD pattern of the unpurified product is shown in [reference needed]. Figure 2 The results showed that, in addition to the target phase (Mo2 / 3Y1 / 3)2AlB2, the sample also contained impurity phases such as MoB, Y2O3, and MoAlB, and possibly a small amount of residual YMoB4 phase. This comparative example was used to characterize the phase composition of the original SHS product and as a control for the effectiveness of subsequent acid washing and stepwise purification.

[0085] Comparative Example 3

[0086] This comparative example is used to investigate the effect of HCl acid washing on the removal or reduction of Y2O3 and MoAlB impurity phases in the original SHS product.

[0087] The original SHS product was prepared according to the method described in Example 1. The product was crushed, ground, and sieved through a 200-mesh sieve. 1 g of the sieved powder was weighed and added to 10 mL of a 2 mol / L HCl solution. The mixture was stirred at 400 rpm for 24 h at room temperature. After treatment, solid-liquid separation was performed by centrifugation, and the supernatant was repeatedly washed with deionized water until the pH was close to 7. The supernatant was then vacuum dried at 60 °C for 24 h. This sample was not subjected to subsequent NaOH / H₂O₂ alkaline oxidation treatment.

[0088] XRD patterns of the HCl-washed products are shown below. Figure 2 Compared to the unpurified product, the diffraction peaks related to Y₂O₃ and MoAlB were significantly weakened or no obvious independent diffraction peaks were detected after acid washing, while the diffraction peaks related to MoB were still present. This result indicates that HCl acid washing can effectively remove or reduce the content of Y₂O₃ and MoAlB impurity phases, but its effect on removing the chemically stable MoB is limited. The unpurified product, the product washed with HCl only, and the final stepwise purified product obtained in Example 1 were compared using the same XRD testing conditions and data processing methods. The results show that HCl acid washing is mainly used to reduce the content of Y₂O₃ and MoAlB impurity phases, while subsequent NaOH / H₂O₂ alkaline oxidation treatment can further reduce the content of residual MoB impurity phases after acid washing, thus demonstrating the targeted effect of the stepwise purification process on different impurity phases.

[0089] The basis for stepwise purification and characterization methods in the above embodiments are as follows:

[0090] (1) In this invention, after self-propagating high-temperature synthesis, HCl acid washing and NaOH / H2O2 alkaline oxidation treatment are sequentially performed. The basis for this treatment sequence is that, under the treatment conditions specified in this invention, Y2O3, MoAlB, and MoB in the crude SHS product exhibit different diffraction peak changes. After HCl acid washing, the diffraction peaks related to Y2O3 and MoAlB are significantly weakened or no obvious independent diffraction peaks are detected, while MoB still exists as the main residual impurity phase; after further NaOH / H2O2 alkaline oxidation treatment, the diffraction peaks related to MoB are further weakened. Therefore, this invention adopts the sequence of acid washing followed by alkaline oxidation to reduce the different impurity phases in stages.

[0091] First, Y₂O₃ reacts with HCl to form soluble yttrium chloride, which enters the liquid phase. The reaction can be represented as: Y₂O₃ + 6HCl → 2YCl₃ + 3H₂O. Therefore, acid washing with 2 mol / L HCl can be used to reduce the content of the Y₂O₃ impurity phase. For the MoAlB impurity phase, HCl may act on its Al-containing structural units; the determination of the effect of this step in this invention is mainly based on the significant reduction or disappearance of the MoAlB-related characteristic peaks in the XRD patterns before and after treatment, and not on unverified microscopic reaction mechanisms as the sole basis.

[0092] Secondly, under the 2 mol / L HCl treatment conditions used in this invention, MoB-related diffraction peaks could still be detected in the sample after acid washing, indicating that the acid washing step had a limited effect on reducing the residual MoB phase. To further reduce the MoB content, this invention employs NaOH / H2O2 alkaline oxidation treatment after HCl acid washing. NaOH provides an alkaline environment, and H2O2 provides oxidation conditions. This treatment may promote oxidation or local dissolution of the MoB surface; the determination of its actual effect in this invention is based on the further weakening of MoB-related diffraction peaks after treatment, while the main characteristic peaks of the target i-MAB phase are still retained.

[0093] It should be noted that the effect of the NaOH / H2O2 alkaline oxidation treatment in this invention is limited to reducing the content of residual MoB impurity phase, not to completely removing MoB. The XRD Rietveld refinement results of the final stepwise purified sample still showed approximately 7.18% residual MoB phase. Further increasing the amount of oxidant, treatment temperature, or treatment time may simultaneously increase the risk of oxidation or corrosion of the target layered boride. Therefore, this invention employs the aforementioned mild treatment conditions to reduce MoB-related diffraction peaks while retaining the main characteristic diffraction peaks of the target i-MAB phase.

[0094] Furthermore, XRD peak comparison showed that some weak diffraction peaks in the original SHS product and the stepwise purified sample corresponded to the YMoB4 candidate phase. Due to the low content of this phase and the overlap of its peak positions with the main phase and MoB, ordinary laboratory XRD data were insufficient to reliably refine its atomic coordinates, site occupancy, and thermal parameters. Therefore, in this invention, YMoB4 was only used as a candidate residual phase in the refined model of the final stepwise purified sample. Its structural parameters were fixed, and only its scale factor was estimated as an auxiliary measure, without refining its atomic positions; the obtained content was only used as an auxiliary semi-quantitative reference.

[0095] (2) To characterize the roles of each stage of self-propagating synthesis and stepwise purification, XRD comparative analysis was performed on the original SHS product, the product washed with HCl only, and the product purified by stepwise purification using HCl washing followed by NaOH / H2O2 alkaline oxidation. The results are shown in […]. Figure 2The three-stage samples employed a consistent testing range, data processing, and normalization method. Phase changes at each treatment stage were evaluated by the appearance, weakening, or disappearance of characteristic peaks. Specifically, the original SHS product was used to identify the target host phase and initial impurity phase; only the HCl acid-washed product was used to characterize changes in Y₂O₃ and MoAlB related diffraction peaks; and the final stepwise purified product was used to characterize changes in MoB related diffraction peaks after NaOH / H₂O₂ treatment. This invention only performed Rietveld refinement on the final stepwise purified sample to determine the relative phase composition of the final product within the range of crystalline phases involved in the refinement. If no independent characteristic peaks of Y₂O₃ and MoAlB were observed after acid washing or stepwise purification, it was stated as "no obvious independent diffraction peaks detected" or "below the conventional XRD detection limit," not as an absolute absence of these peaks.

[0096] In addition to XRD comparison and major phase content analysis, SEM and EDS mapping can be used to assist in the characterization of the stepwise purified products, which can be used to verify the distribution of target elements in representative particles and local stoichiometry. EDS results are only used as evidence of local component and element co-distribution; the overall crystalline phase and target phase content of the sample are still based on XRD and Rietveld analysis results.

[0097] In summary, under the self-propagating synthesis conditions employed in this invention, the Mo-Y-Al-B reaction raw materials can form a crude product with (Mo2 / 3Y1 / 3)2AlB2 i-MAB as the main phase. Simultaneously, impurity phases such as MoB, Y2O3, and MoAlB can be detected, possibly accompanied by a small amount of YMoB4 candidate residual phase. Due to the different responses of these impurities to different chemical media, under the processing conditions defined in this invention, single acid washing is insufficient to simultaneously reduce all types of impurities. After treatment with 2 mol / L HCl at room temperature for 24 h, the diffraction peaks related to Y2O3 and MoAlB are significantly weakened or no obvious independent diffraction peaks are detected, while the diffraction peak related to MoB still exists. Further alkaline oxidation treatment with NaOH / H2O2 further weakens the MoB-related diffraction peak, and the main characteristic diffraction peaks of the target i-MAB phase are still retained.

[0098] As described above, although the invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the invention itself. Various changes in form and detail may be made without departing from the spirit and scope of the invention.

Claims

1. A method for the self-propagating synthesis and stepwise purification of (Mo2 / 3Y1 / 3)2AlB2 i-MAB material, characterized in that, Includes the following steps: S1. Weigh Mo powder, Y powder, Al powder and B powder according to the molar ratio Mo:Y:Al:B=4:2:3(1+x):6, mix them to obtain the Mo-Y-Al-B reaction raw material system, and then ball mill the mixture. Where x is greater than 0. Preparation of S2 and Ti-C assisted exothermic system; S3. The Mo-Y-Al-B reaction raw material system is filled into the central region of the crucible, and the Ti-C auxiliary exothermic system is filled into the surrounding region of the crucible; S4. Under an argon atmosphere, the Ti-C assisted exothermic system is ignited by an external electric ignition to induce an exothermic reaction. The heat released by the Ti-C assisted exothermic system is used to induce a self-propagating high-temperature synthesis reaction in the Mo-Y-Al-B reaction raw material system to obtain a crude synthetic product containing the (Mo2 / 3Y1 / 3)2AlB2 i-MAB main phase. S5. The crude synthetic product is pulverized, and the pulverized product is placed in HCl solution for acid washing. After solid-liquid separation, the acid-washed solid product is obtained. S6. Place the acid-washed solid product in a NaOH / H2O2 mixed solution for alkaline oxidation treatment; S7. The solid product after alkaline oxidation treatment is washed, separated into solid and liquid and dried to obtain (Mo2 / 3Y1 / 3)2AlB2i-MAB material.

2. The method according to claim 1, characterized in that, In S1, x ranges from 4% to 30%.

3. The method according to claim 1, characterized in that, In S4, the ignition voltage of the electric ignition method is 5-40V, the ignition time is 1min, and the ignition voltage is preferably 10V.

4. The method according to claim 1, characterized in that, In step S5, the concentration of the HCl solution is 2 mol / L, and the solid-liquid ratio of the synthesized crude product to the HCl solution is 1 g: 10 mL. Acid washing is carried out at room temperature, with a stirring rate of 400 r / min and a washing time of 24 h.

5. According to the method of claim 1, in S6, the NaOH / H2O2 mixed solution is prepared according to the following ratio: 67 mL of deionized water, 0.43 g of NaOH with a purity of 97% and 2.8 mL of H2O2 with a mass fraction of 30% for every 1 g of the acid-washed solid product. The alkaline oxidation treatment temperature is room temperature, the stirring rate is 400 r / min, and the treatment time is 4 h.

6. The method according to claim 1, characterized in that, In S2, a Ti-C assisted exothermic system composed of Ti powder and C powder is set up, with a molar ratio of Ti to C of 1:

1.

7. The method according to claim 6, characterized in that, In S1, the purity of Mo powder, Y powder, Al powder, and B powder is not less than 99.9%, and the particle size is 300 mesh or equivalent. In S2, the purity of Ti powder and C powder is 99.9%, and the particle size is 300 mesh or equivalent. The Mo-Y-Al-B reaction raw material system and the Ti-C auxiliary exothermic system were ball-milled and sieved for later use. The ball-milling and sieving parameters were as follows: a planetary ball mill was used for ball milling and mixing, the ball-to-material ratio was 3:1, the ball milling speed was 240 r / min, the ball milling time was 6 h, argon gas was introduced for 20 min before ball milling, and the mixture was sieved through a 200 mesh sieve after ball milling.

8. The method according to claim 1, characterized in that, In S5, the collected crude synthetic product is crushed, ground, and passed through a 200-mesh sieve. The powder that passes through the sieve is then placed in an HCl solution for acid washing.

9. The method according to claim 1, characterized in that, In step S7, the solid product after alkaline oxidation is washed with deionized water until the pH is close to 7; the solid-liquid separation is carried out by centrifugation at a speed of 3000-8000 r / min and a single centrifugation time of 2-5 min; the vacuum drying temperature is 50-80℃ and the drying time is 24 h.

10. The (Mo2 / 3Y1 / 3)2AlB2 i-MAB material prepared by the method according to any one of claims 1-9, characterized in that, In the (Mo2 / 3Y1 / 3)2AlB2 i-MAB material, the content of the (Mo2 / 3Y1 / 3)2AlB2 i-MAB phase is not less than 90%.